Investigating tropospheric radio refractivity variation with weather parameters in Kampala, Uganda: implications for communication systems - Bawa, Musa; Afam Uzorka,; Living Ounyesiga ,; Tukur, Rabiu (International Journal of Physical Research, 2024)
The tropospheric radio refractivity plays an important role in the propagation of radio waves and significantly affecting the performance of radio communication systems. This study aims to investigate the influence of weather parameters on tropospheric radio refractivity variation and the implication for communication system in Kampala, Uganda. Through a comprehensive dataset of temperature, humidity and pressure obtained from the National Aeronautics and Space Administration (NASA) archives for Kampala over a period of one year (January 2023 to December 2023). Using the International Telecommunication Model (ITU-R model), radio refractivity was computed from the collected weather parameters, and subsequently correlate with weather parameters. The analyses of the results showed that, radio refractivity displayed seasonal variability with high values in the wet season with a peaks points observed in April and October (339N and 338N) and a low value during dry season, July and January (328N and 324). It was also observed that the Relative humidity and Temperature are the main force driven the variations of radio refractivity. Hence, the work could be used for rapid and precise estimation of link budgets while planning and designing radio links budget in Kampala and regions of similar climatic characteristics.